Modulating heterologous pathways and optimizing fermentation conditions for biosynthesis of kaempferol and astragalin from naringenin in Escherichia coli. (1st February 2019) - Pei, Jianjun; Chen, Anna; Dong, Ping; Shi, Xuejia; Zhao, Linguo; Cao, Fuliang; Tang, Feng
Abstract: Kaempferol and astragalin are used as standards to assess the quality of Ginkgo biloba extract and Radix astragali, respectively, and possess numerous biological properties. In this study, we constructed a recombinant strain with a highly efficient biosynthetic pathway of kaempferol by screening key enzyme genes, designing a synthetic fusion enzyme and increasing the gene copy number. By optimizing conversion and fed-batch fermentation conditions, maximal kaempferol production reached 1184.2 ± 16.5 mg/L, which represents the highest yield of kaempferol from naringenin reported to date. Based on this result, glycosyltransferase (AtUGT78D2) and an efficient UDP-glucose synthesis pathway were introduced into the recombinant strain to produce astragalin, resulting in maximal astragalin production at 1738.5 ± 24.8 mg/L without kaempferol accumulation. The efficient synthesis pathway described in this study for kaempferol and astragalin biosynthesis can be widely used for flavonoid biosynthesis in Escherichia coli .